Pengelolaan dan Pertanggungjawaban Pemerintah dalam Menanggulangi Penebangan Hutan Liar di Indonesia: Studi Kasus Katingan, Kalimantan Tengah - Rayi Kharisma Rajib; Vodena Selena Junior; Dzalzala Belia Nadzwa Krisvianthania (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Illegal logging practices in Katingan Regency, Central Kalimantan, remain a grim portrait of systemic environmental crime. These illegal activities not only destroy the ecosystem's carrying capacity and trigger a local climate crisis, but also undermine the country's economic stability and threaten the living spaces of indigenous communities. Using normative juridical methods and in-depth literature review, this study seeks to map the complexity of the causal factors and evaluate the extent to which legal enforcement has been enforced in the region. Illegal logging in Katingan is driven by the conflict between high global market demand and the economic hardships of communities surrounding forest areas. This situation is exacerbated by minimal oversight in remote areas, limited personnel, and the shadow of corruption in forestry licensing mechanisms. Constitutionally, Indonesia has legal safeguards in place through Law No. 41 of 1999 and Law No. 18 of 2013. However, the reality on the ground shows that law enforcement is often hampered by geographical barriers and an inefficient bureaucratic structure. As a solution, a policy reorientation is needed that does not only rely on criminal sanctions, but also prioritizes improved governance, synergy between agencies, and concrete community empowerment programs to ensure the sustainability of forests in the future.